Identification and Characterization of Malaysian River Catfish, Mystus nemurus (C&V): RAPD and AFLP Analysis - Chong, L. K.; Tan, S. G.; Yusoff, K.; Siraj, S. S. (Springer, 2000)
This work represents the first application of the amplified fragment length polymorphism (AFLP) technique and the random amplified polymorphic DNA (RAPD) technique in the study of genetic variation within and among five geographical populations of M. nemurus. Four AFLP primer combinations and nine RAPD primers detected a total of 158 and 42 polymorphic markers, respectively. The results of AFLP and RAPD analysis provide similar conclusions as far as the population clustering analysis is concerned. The Sarawak population, which is located on Borneo Island, clustered by itself and was thus isolated from the rest of the populations located in Peninsular Malaysia. Both marker systems revealed high genetic variability within the Universiti Putra Malaysia (UPM) and Sarawak populations. Three subgroups each from the Kedah, Perak, and Sarawak populations were detected by AFLP but not by RAPD. Unique AFLP fingerprints were also observed in some unusual genotypes sampled in Sarawak. This indicates that AFLP may be a more efficient marker system than RAPD for identifying genotypes within populations.